VALIDATION OF BIOLOGICAL ACTIVITIES AND CHARACTERIZATION OF EXTRACTS OF Anaphalis margaritacea (L.) BENTH. AND HOOK.F. FROM HILLY TERRAINS OF UTTARAKHAND HIMALAYA - ARTI,; BAHUGUNA, ANANYA; ARYA, ARADHANA; DUBEY, SHIV KUMAR; SINGH, KAMANA; KUMAR, RAVENDRA; PRAKASH, OM; RAWAT, DHARMENDRA SINGH; ARYA, PRABHA (The Bioscan, 2023)
The paper focuses on the biological activities of polar and non-polar extracts made from the aerial part of the plant Anaphalis margaritacea that was further chemically characterized. Both extracts’ constituent components were identified by their GC-MS profiles. In vitro antioxidant and anti-inflammatory activity of methanolic and hexane extracts was further investigated. The methanolic extract showed the identification of twenty-eight compounds that constituted 83.29% of the total methanolic extract of which 5R, 8R, 9S, 10R)-2-Formyl-3-Hydroxy-5Isopropeny-8-8Methyl (3a10)-octahydronaptho (13.15%) was identified as the major compound. Identified compounds constituted 51.88% of the total composition of the hexane extract with hexatriacontane as one of the most prominent compounds occupying 20.43%. When compared to hexane extract, the methanolic extract revealed lower IC50 values for DPPH radical scavenging activity (75.94±0.66 µg/mL), metal chelating activity (72.90±0.096 µg/mL), and reducing power activity (79.64±5.360 µg/mL) demonstrating that it possesses strong antioxidant potential. Additionally, methanolic extract demonstrated better anti-inflammatory properties, with an IB50 value of 37.581±050 g/mL. Based on these results, methanolic extract appears to be a more potent antiinflammatory and antioxidant agent than hexane extract.